2021
DOI: 10.1016/j.redox.2021.102105
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Regulator of G Protein Signaling 6 (RGS6) drives non-alcoholic fatty liver disease by promoting oxidative stress and ATM-dependent cell death

Abstract: The pathophysiological mechanism(s) driving non-alcoholic fatty liver disease, the most prevalent chronic liver disease globally, have yet to be fully elucidated. Here, we identify regulator of G protein signaling 6 (RGS6), up-regulated in the livers of NAFLD patients, as a critical mediator of hepatic steatosis, fibrosis, inflammation, and cell death. Human patients with high hepatic RGS6 expression exhibited a corresponding high inflammatory burden, pronounced insulin resistance, and poor liver function. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Studies have shown that FOXN3 suppresses the mRNA and protein expression of E2F5 by inhibiting the promoter activity of potential oncogene E2F5 , thereby inhibiting the proliferation of HCC cells in vitro and in vivo ( 43 ). Another tumor suppressor, regulator of G protein signaling 6 ( RGS6 ), is upregulated in the liver of NAFLD patients, forms a complex with ATM in the liver, promotes ATM phosphorylation, and drives hepatic steatosis ( 44 , 45 ). A study confirmed that hepatic RGS6 increases oxidative stress and inflammation, which drive lipid deposition, fibrosis, and nonalcoholic fatty liver disease ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that FOXN3 suppresses the mRNA and protein expression of E2F5 by inhibiting the promoter activity of potential oncogene E2F5 , thereby inhibiting the proliferation of HCC cells in vitro and in vivo ( 43 ). Another tumor suppressor, regulator of G protein signaling 6 ( RGS6 ), is upregulated in the liver of NAFLD patients, forms a complex with ATM in the liver, promotes ATM phosphorylation, and drives hepatic steatosis ( 44 , 45 ). A study confirmed that hepatic RGS6 increases oxidative stress and inflammation, which drive lipid deposition, fibrosis, and nonalcoholic fatty liver disease ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of TAK1 and its downstream signaling significantly promotes liver injury, inflammation, fibrosis, and tumor formation (Inokuchi et al ., 2010; Tan et al ., 2020). TAK1 hyperactivation, on the other hand, induces hepatic steatosis, inflammation, and fibrosis, whereas TAK1 activity suppression alleviates the progression of these diseases (Inokuchi et al ., 2010; Mahata et al , 2021; Qian et al ., 2022; Zhang et al ., 2022). Here, TAK1 inhibition attenuated JNK activation, restored the eNOS level, and down-regulated cytokines and adhesion molecule in Txnip -deficient LSECs.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Gβ 5 KD in murine VCM blocks doxorubicin- and 5-FU-driven phosphorylation of both ATM and CaMKII. RGS6, which forms a direct complex with ATM [ 36 ] is required for activation of the ATM/p53 signaling cascade in VCM exposed to doxorubicin [ 31 ], but the R7 family member responsible for CaMKII regulation had yet to be identified. Indeed, the fact that Gβ 5 expression is not completely absent from the hearts of RGS6 −/− mice [ 56 , 57 ] indicates that another R7 family member is also present in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…The full-length RGS11 and CaMKIIδ coding sequences were amplified by PCR from human blood cDNA according to our published method [ 36 ]. RGS11 and CaMKIIδ deletion & point mutation sequences were generated by overlapping primer-based PCR amplification and cloned into the pEGFP-N1 vector or pCMV-HA-N vectors, respectively.…”
Section: Methodsmentioning
confidence: 99%